PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN DI PT. PERKEBUNAN NUSANTARA IV BAH JAMBI - Maulida Neza Hayati Sitompul; Susilawati (Jurnal Kesehatan, 2024)
Occupational Health and Safety is an important matter that must be seriously considered in construction work to minimize the potential for work accidents, material and moral losses which will later be used to support effective and efficient performance improvements. PTPN VI has buildings with various forms and different functions and very busy work activities, so it is very important to take into account preparedness in dealing with emergencies so that excessive panic, losses and even fatalities do not occur. In the production environment, work accidents still occur on a moderate to severe scale. The purpose of this study is to find out how the implementation of the Occupational Health and Safety Management System (SMK3) is described. Data collection for this study was carried out through observation of the field and work environment as well as distributing questionnaires to respondents. The results of the study show that all procedures in dealing with emergencies have been complied with and carried out by the management of the Occupational Health and Safety Advisory Committee (P2K3) in accordance with the provisions stipulated by Government Regulation Number 50 of 2012 concerning Implementation of the Occupational Safety and Health Management System (SMK3)